THE NEW AVENGERS: THE ROLE OF SOCIAL JUSTICE AND TEAMWORK IN DIGITAL ACTIVISM – A LITERATURE REVIEW - Serly Andriani Kusnadi; Herdiyan Maulana; Zarina Akbar (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
ABSTRACT Obstacles to channeling conventional political aspirations and the prevalence of systemic discrimination in the public sphere are the background to this article. These issues trigger sociopsychological alienation, which drives the emergence of independent collective movements in cyberspace. The main focus of this theoretical study is to comprehensively explore the central role of social justice and teamwork in mapping the phenomenon of digital movements driven by a new generation of activists called The New Avengers. The research steps were carried out using a narrative literature review method that adopted the selection principles of the PRISMA framework. The secondary data screening procedure systematically synthesized twenty original scientific articles from Scopus, PsycINFO, and Google Scholar databases published over the past ten years. Thematic synthesis-based research findings indicate that the principle of social justice serves as a core motivation and fundamental goal of the movement. Digital platforms have proven to provide powerful tools for narrative amplification, fostering solidarity among marginalized groups, and coordinating collective action in real time. The main conclusion emphasizes that although cyberspace offers freedom of expression, the success of digital activism is heavily influenced by cyber structural barriers, the threat of antagonism, and the repressive dynamics of authoritarian networks. Activists are recommended to draft a strategy to strengthen critical media literacy and inclusive collaborative ethics to ensure the sustainability of the impact of social change.   ABSTRAK Hambatan penyaluran aspirasi politik konvensional serta maraknya diskriminasi sistemik di ruang publik melatarbelakangi penulisan artikel ini. Masalah tersebut memicu alienasi sosiopsikologis yang mendorong munculnya gerakan kolektif independen di ruang siber. Fokus utama kajian teoretis ini adalah mengeksplorasi secara komprehensif peran sentral keadilan sosial serta kerja sama tim dalam memetakan fenomena pergerakan digital yang digerakkan oleh generasi aktivis baru bernama The New Avengers. Langkah-langkah penelitian dijalankan menggunakan metode tinjauan literatur naratif (narrative literature review) yang mengadopsi prinsip seleksi kerangka kerja PRISMA. Prosedur penyaringan data sekunder secara sistematis menyintesis dua puluh artikel ilmiah orisinal dari basis data Scopus, PsycINFO, dan Google Scholar dalam rentang publikasi sepuluh tahun terakhir. Temuan riset berbasis sintesis tematik menunjukkan bahwa prinsip keadilan sosial berfungsi sebagai motivasi inti dan tujuan fundamental pergerakan. Platform digital terbukti menyediakan alat yang ampuh untuk amplifikasi narasi, penggalangan solidaritas kelompok marjinal, serta koordinasi tindakan kolektif secara real-time. Simpulan utama menegaskan bahwa meskipun ruang siber menawarkan kebebasan ekspresi, tingkat keberhasilan aktivisme digital sangat dipengaruhi oleh hambatan struktural siber, ancaman antagonisme, dan dinamika represi jaringan otoriter. Para aktivis direkomendasikan menyusun draf strategi penguatan literasi media kritis dan etika kolaborasi inklusif demi menjamin keberlanjutan dampak perubahan sosial.